Planes of progression: an exploration of architecture's role in supporting the positive development of youth from disadvantaged backgrounds - Mativenga, Tapiwanashe Emmanuel (School of Architecture, Planning and Geomatics, 2018)
Youth from disadvantaged backgrounds develop at a slower rate than youth from well-to-do neighborhoods. They do not reach the same levels of development and are often kept within the unforgiving grip of poverty. The problem is compounded by the rising rate of urbanisation and informal settlements with slum conditions. Youth in these areas bear the consequences of such backgrounds; their development is hindered due to the absence of resources and spaces of youth development. In cases where those spaces are present, the quality of design, construction and maintenance makes them unappealing and less effective. A key concern is the lack of awareness and ease of access to these spaces by youth at risk in the area. This design dissertation explores how architecture and good design can be utilised to improve presence, access and utilisation of youth development spaces at three different scales, the urban, the street and the building edge. Using the Gugulethu Township in Cape Town, the design dissertation examines and develops a network of youth development distributed over five sites. This increases institutional presence and youth access. These sites use carefully articulated planes, strategically arranged to achieve a positive and appealing presence in the area. The planes allow permeability of youth off the street into the development space, separation of different levels of development and enable the buildings to utilise a cost effective approach to achieving thermal comfort.